Prevalence of intestinal colonization and nosocomial infection with carbapenem-resistant Enterobacteriales in children: a retrospective study - Pan, Fen; Chen, Pengcheng; Duan, Yuxin; Yu, Fangyuan; Weng, Wenhao; Zhang, Hong (Frontiers in Public Health, 2023)
Objective: We investigated the epidemiological surveillance of the intestinal colonization and nosocomial infection of carbapenem-resistant Enterobacteriales (CRE) isolates from inpatient, which can provide the basis for developing the effective prevention.Methods: A total of 96 CRE strains were collected from 1487 fecal samples of hospitalized children between January 2016 and June 2017, which was defined into "CRE colonization" group. 70 CRE clinical isolates were also randomly selected for the comparison analysis and defined as "CRE infection" group. Antimicrobial susceptibility of all strains was determined by microdilution broth method. Polymerase chain reaction (PCR) was used to analyze carbapenemase genes, plasmid typing, and integrons. Multilocus sequence typing was further used to determine clonal relatedness.Results: Among "CRE colonization" group, K. pneumoniae were mostly detected with a rate of 42.7% (41/96), followed by E. coli (34.4%, 33/96), E. cloacae (15.6%, 15/96). The ST11 KPC-2 producer, ST8 NDM-5 producer, and ST45 NDM-1 producer were commonly in carbapenemresistant K. pneumoniae (CRKPN), carbapenem-resistant E. coli (CRECO), and carbapenemresistant E. cloacae (CRECL) isolates, respectively. Among "CRE infection" group, 70% (49/70) of strains were K. pneumoniae, with 21.4% E. cloacae (15/70), 5.7% E. coli (4/70). The ST15 OXA-232 producer and ST48 NDM-5 producer were frequently in CRKPN isolates, while majority of NDM-1 producing CRECL isolates were assigned as ST45. Phylogenetic analysis showed that partial CRE isolates from intestinal colonization and nosocomial infection were closely related, especially for ST11 KPC-2 producing CRKPN and ST45 NDM-1-prodcuing CRECL. Furthermore, plasmid typing demonstrated that IncF and IncFIB were the most prevalent plasmids in KPC-2 producers, while IncX3/IncX2 and ColE were widely spread in NDM-producer and OXA-232 producer, respectively. Then class 1 integron intergrase intI1 was positive in 74.0% (74.0%, 71/96) of "CRE colonization" group and 52.9% (37/70) of "CRE infection" group.This study revealed that CRE strains from intestinal colonization and nosocomial infection showed partial correlation in the prevalence of CRE, especially for ST11 KPC-2 producing CRKPN and ST45 NDM-1-prodcuing CRECL. Therefore, long-term active screening of rectal colonization of CRE isolates prior admission should be emphasized.